Determination of chlorophyll and nitrogen content in rice leaves at various growth stages - Saberioon, Mohammadmehdi (2014)
Nitrogen (N) is an important input variable for rice farming. Concerns over the use of nitrogen have increased due to the increase in fertilizer costs and environmental pollution from excess nitrogen applications in paddy fields. Several methods are available to assess nitrogen in crops. However, they are either expensive, time consuming, inaccurate or needs specialists to operate the tools. Recently researchers suggest remote sensing of chlorophyll content in crop canopies as a low-cost alternative to determine plant N status. Among different remote sensing platforms, low altitude remote sensing (LARS), which is a relatively new concept of acquiring earth imagery at a low altitude using unmanned aerial vehicle (UAV), is an attractive method and being promoted by researchers to determine status of chlorophyll content and nitrogen in rice field. The high spatial and temporal resolution, fast way to collect data and relatively low data acquisition cost would suggest this platform as ideal tool for monitoring crops through out the plant‟s growth. Furthermore, researchers have found that visible wavelengths would be useful for determining nutrient status and biomass in crops. Thus, the main objective of this study was to develop and test new methods for determining the status of chlorophyll content and N in rice leaf by analyzing and considering information derived from the images captured using conventional digital cameras (Panasonic Lumix DMC-TZ10 and Basler Scout scA640-70fc) and a new generation of multispectral camera (Tetracam ADC). Digital photographs of the upper most collared leaf of rice (Oriza sativa L.) in both leaf and canopy scale, grown over a range of N treatments, were processed into all published indices and also IPCA, which is a new index for rice developed in this study based on utilizing all three visible bands and principal component analysis. Also conventional digital camera mounted to an UAV was used to acquire image over the rice canopy for verification purpose. The results indicate that conventional digital camera (r = -0.81) and Tetracam ADC (r = 0.89) could be used as sensors to determine the status of chlorophyll content in rice plants through different growth stages. Also IPCA shows significant negative correlation not only in leaf scale (r = -0.81) but also in canopy scale when UAV was utilized to capture images (r = -0.78). This indicates that conventional low-cost digital cameras and Tetracam ADC cameras, both can be used for determining chlorophyll content and consequently monitor Chlorophyll and N content of the growing rice plants, and also offers a potentially inexpensive, fast, accurate and suitable tool for rice growers. Additionally, results exhibited that a low cost LARS system would be well suited for high spatial and temporal resolution images and data analysis for proper assessment of key nutrients in rice farming in a fast, inexpensive and non-destructive way. Hence, the results of this study could be a significant contribution to develop the site-specific management decision for in-season, variable rate fertilizer application towards sustainable agriculture.